Synchronized activity of organic cation transporter 3 (Oct3/Slc22a3) and multidrug and toxin extrusion 1 (Mate1/Slc47a1) transporter in transplacental passage of MPP+ in rat - Ahmadimoghaddam, Davoud; Hofman, Jakub; Zemankova, Lenka; Nachtigal, Petr; Dolezelova, Eva; Cerveny, Lukas; Ceckova, Martina; Micuda, Stanislav; Staud, Frantisek (Toxicological sciences, 2012)
The aim of the present study was to investigate the expression, localization, and function of organic cation transporter 3 (Oct3, Slc22a3) and multidrug and toxin extrusion protein 1 (Mate1, Slc47a1) in the rat placenta. Using qRT-PCR and Western blotting techniques, we demonstrated abundant Oct3 and Mate1 mRNA and protein expression achieving significantly higher levels than those in the maternal kidney (positive control). Immunohistochemical visualization revealed preferential localization of Oct3 on the basolateral, i.e., fetus facing side of the placenta, whereas Mate1 positivity was located in the labyrinth area predominantly on the apical, i.e., maternal side of the placenta. To investigate the role of these transporters in the transplacental pharmacokinetics, the in situ method of dually perfused rat term placenta was employed in open- and closed-circuit arrangements; 1-methyl-4-phenylpyridinium (MPP(+)) was used as a model substrate of both Oct3 and Mate1. We provide evidence that Oct3 and Mate1 cause considerable asymmetry between maternal-to-fetal and fetal-to-maternal transport of MPP(+) in favor of fetomaternal direction. Using closed-circuit experimental setup, we further describe the capacity of Oct3 and Mate1 to transport their substrate from fetus to mother even against a concentration gradient. We conclude that Oct3, in a concentration-dependent manner, takes up MPP(+) from the fetal circulation into the placenta, whereas Mate1, on the other side of the barrier, is responsible for MPP(+) efflux from placenta to the maternal circulation. These two transport proteins, thus, form an efficient transplacental eliminatory pathway and play an important role in fetal protection and detoxication.
Keywords: Cell Line; Rats, Wistar; Organic Cation Transport Proteins; proteiny přenášející organické kationty; 1-Methyl-4-phenylpyridinium; Pregnancy; těhotenství; Antiporters; Placenta; imunohistochemie; potkani Wistar; polymerázová řetězová reakce s reverzní transkripcí; antiportéry; krysa rodu Rattus; Maternal-Fetal Exchange; maternofetální výměna látek; placenta; Animals; ženské pohlaví; Immunohistochemistry; 1-methyl-4-fenylpyridinium; zvířata; Rats; Reverse Transcriptase Polymerase Chain Reaction; buněčné linie; Female